Desain Sistem Pengukuran Parameter dan Keamanan Penerangan Jalan Umum Tenaga Surya Berbasis Internet of Thing (IoT) - Toh-arlim, Muhaimin; Ma'arif, Alfian; Anggari Nuryono, Aninditya (Majalah Ilmiah Teknologi Elektro; Vol 20 No 2 (2021): (Juli-Desember) Majalah Ilmiah Teknologi Elektro, 2021)
This study proposes a monitoring system for voltage, current, power and safety of solar street lighting (PJUTS) using mobile phones and the Internet of Things (IoT) based Blynk application. Public street lights that are damaged and prone to theft require monitoring and security systems. As a measurement of voltage, current and power, the INA219 current sensor is used. The sensor value will be read by the NodeMCU microcontroller and sent with IoT to be displayed in the Blynk application on the cellphone so that the processed information can be seen. PIR sensors and ultrasonic sensors are used to identify and detect objects around PJUTS lamps so that they can function as safety for street lights. In the estimation of battery charging, the solar cell gets the highest light at the estimated 12:00-13:00 with a value of 99800 and produces 6.97 watts of power, with a voltage of 11.8 volts and a current of 0.6 amperes. The farthest distance a PIR sensor can identify the progress of an object is 5 meters. The size of the data sent to Blynk within 24 hours is 119.16MB.